Nudging with Framing, Defaults and Social References in the Context of Online Privacy Decision-Making - Kochendörfer, Laura (My University, 2021)
As a result of rapid technological progress, vast opportunities to create, share, transfer or gather data arise. Concomitantly, individuals face unprecedented challenges navigating decisions about data disclosure in online spheres and privacy concerns increase accordingly. Nudges are choice architectural instruments to aid challenging online privacy decision-making by steering individuals’ decisions towards a particular direction. Present research identifies nudges for online privacy decision-making and examines framing, default, or social reference nudges in particular with regard to the effects they exhibit on individuals online privacy decision-making. Digital nudges for online privacy decision-making as well as their effects are derived from empirical literature. Based upon the literature review, the thesis proposes a conceptual framework, categorizing factors affecting nudge effectiveness. Results show that framing, defaults, and particularly social references exhibit different and even opposing effects in various online privacy decision-making contexts. External and internal factors, such as government regulation, group belonging, emotion, or need for cognition seem to have an impact on the effectiveness of said nudges. Importantly, influencing factors are differently pronounced according to different privacy contexts or different types of nudges. Derived propositions on particular nudges conducive for enhanced online privacy decision-making towards greater data protection constitute a valuable contribution. With currently scant behavioral economics research devoting attention to online privacy decision-making, this thesis further advances research towards a better conceptualization of nudging for online privacy. A discussion on ethics of nudging and limitations of nudges as a regulatory instrument puts practicality of nudging approaches into perspective and likewise establishes theoretical criticism.
Keywords: Nudging, Privacy, Online Privacy Decision-Making, Framing, Default, Social Reference